Influence of Electrophoretic Deposition (EPD) voltage on SOFC interconnect morphology - Lowrance, Yohannes Nyambong; Azmi, Mohd Azham; Abdul rahman, Hamimah; Abdul Rahman, Nurul Farhana; Zakaria, Hanis; Hassan, Suhaimi (2022)
Solid oxide fuel cell has become one of the interest in the sustainable energy field. In order to improve the efficiency of a solid oxide fuel cell (SOFC), the interconnect must be coated with a protective coating of (MnCO)3O4 spinel coated stainless steel. Commercial manganese cobalt (MnCO)3O4 was used as a protective coating on ferritic stainless steel in this study using the electrophoretic deposition (EPD) coating technique. This article examines the impact of voltage deposition towards morphological characteristics. The goals of these studies are to find the best interconnect coating parameter while experimenting with voltage deposition. The spinel coated interconnect (MnCO)3O4 was studied using Elemental Energy Dispersive X-ray Spectroscopy (EDS). The surface morphology and coating thickness are examined using a Scanning Electron Microscope (SEM). X-ray diffraction (XRD) is used to determine the phase of the spinel coated interconnect. The EPD coating technique for (MnCO)3O4 spinel coated interconnect is carried out in an aqueous suspension with 30V and 40V with coating durations of 20s, 30s, 40s, 50s, and 60s. By observing the deposition morphology and thickness coating at 30V and 40V, the best covering parameter for interconnect is 30V, 40s which fulfil the interconnect requirement of ASR value below 0.1